Financing marine conservation tourism: Governing entrance fees in Raja Ampat, Indonesia. (April 2017) - Atmodjo, Ery; Lamers, Machiel; Mol, Arthur
Abstract: Worldwide, the growth of marine tourism is creating opportunities for financing marine protected areas (MPAs), but what these financial arrangements look like and how they can be governed at larger scales, and in equitable and transparent ways, is unclear. This paper examines the governance arrangement of two region-wide successive entrance fee systems established since 1997 in Raja Ampat, Indonesia, to finance a network of MPAs delineated under the auspices of two big international non-governmental organizations (NGO), namely Raja Ampat Entrance Fee and Raja Ampat Ecosystem Service Stewardship Fee. These two successive entrance fee systems can be viewed as payment for environmental services (PES) arrangements. The PES-like entrance fee arrangements improved in terms of participation, transparency and equity. In the second scheme, local communities in Raja Ampat were involved in the design of the disbursement of the community fund, and the criteria for disbursement became more clear and transparent. However, in both schemes there is no clear connection between the distribution of the funds and activities that improve environmental services provision (conditionality). In addition, the latter scheme is still facing equity challenges as some communities with customary rights over marine tourism hotspots are asking for additional user-fees from tourists and tourism operators.